TREATMENT OF EARLY STAGES HODGKIN LYMPHOMA DURING PREGNANCY - Agustin Avilès; Maria-Jesus Nambo; Natividad Neri (Mediterranean Journal of Hematology and Infectious Diseases)
Objetive. To assess maternal and fetal outcome of women who receiving chemotherapy during pregnancy to treat Hodgkin lymphoma(HL) in early stages (IA and IIA), we performed an retrospective analysis of 44 women with HL at early stage, diagnosed and treated between 1988 to 2010, in a tertiary reference cancer center.